Hubungan Pengetahuan Ibu Hamil Tentang Gizi dengan Kejadian Kurang Energi Kronik (KEK) di Puskesmas Tempunak - Tessa Julia Tifania; Zesika Intan Navelia; Siti Fadhilah (Jurnal Siti Rufaidah, 2025)
heritage: persistent power Deficiency (CED) among pregnant women is a dietary problem that may have an effect on both maternal and fetal fitness. one of the influencing factors is the mother’s nutritional know-how. This look at aimed to investigate the relationship between nutritional knowledge and the prevalence of CED amongst pregnant ladies in the running area of Tempunak clinic. take a look at methods: This study employed an analytic observational design with a pass-sectional technique. The population consisted of 88 pregnant girls selected the use of purposive sampling. studies gadgets blanketed a dietary understanding questionnaire and Mid-higher Arm Circumference (MUAC) measurement to decide CED fame. statistics analysis turned into executed the use of univariate analysis within the form of frequency distribution, and bivariate analysis with the Chi-rectangular check. effects: maximum respondents had exact nutritional information (fifty nine.09%), and greater than 1/2 did not experience CED (55.68%). The Chi-square check received a p-cost of 0.000 (<zero.05) with a Chi-square fee of 30.410, indicating a massive relationship between dietary knowledge and CED. Pregnant ladies with top dietary understanding were much less in all likelihood to enjoy CED, even as all respondents with terrible information skilled CED. end: there's a large courting between dietary understanding and the incidence of CED amongst pregnant girls. continuous dietary training is vital to lessen the risk of CED and enhance maternal fitness.